DIFFERENCES OF AGE AND GENDER IN PITCH RANGE MODULATION IN YES-NO QUESTIONS IN EKEGUSII (The University of Nairobi Journal of Language and Linguistics, 2023)
The aim of the paper was to describe pitch range modulation in yes-no questionsin Ekegusii. In addition to describing the realization of intonation-relatedfeatures like upstep and fundamental frequency (F0) in these questions, thepaper has related this realization to the age and gender variables, to show howvaried speakers’ speech is acoustically different. Data were collected from 24purposively selected native speakers of Ekegusii (12 male and 12 female ofdifferent age groups). They were analysed within the framework of theAutosegmental-Metrical Theory. Two findings emerged from the analysis. First,the male speakers’ pitch range modulation was realised at an F0 bottom line of126 Hz and top line of 242 Hz while the female speakers’ F0 bottom line was 225Hz and top line 260 Hz. Second, although female speakers produced theutterances at higher F0s than their male counterparts did, there were variationsacross the four age groups of male and female speakers. The largest variation inF0 occurred among the youth and the smallest among the children. Theadvanced-aged female group of participants and the male children’s groupproduced the highest F0s while the middle-aged groups (both the female and themale) produced the lowest F0.